Strategi Guru PAK dalam Membangun Pancasila sebagai Paradigma Integrasi Bangsa terhadap Peserta Didik di Era Milenial - Reni Triposa; Yonatan Alex Arifianto (Jurnal Teologi Berita Hidup, 2021)
Abstract: Without realizing it, the millennial era with technological sophistication brings students to be influenced by wrong associations which will unconsciously bring about the disintegration of the nation. Therefore, teachers of Christian religious education can have strategies in bringing students to build their nationality through the paradigm of national integration based on Pancasila. through technological advances. and having used descriptive qualitative methods with a literature study approach, it can be concluded that the PAK teacher's strategy in building Pancasila as a paradigm of Nation integration towards students in the millennial era is to understand the degradation or moral decadence in the millennial era which continues to increase. For this reason, Christian Religious Education Teachers actualize the view of Pancasila as the basis for developing the integration of the Nation and also see that there is no theological debate on the value of Pancasila in the theological ethical perspective. From this, teachers have the basis to play a role in Guru Pak's strategy in the Actualization of National Integration in the millennial era, with the following steps: First, they are able to grow the faith of students who are increasingly mature. Second, it teaches to love each other and get rid of all bullying and improper behavior of students in respecting their nation's leaders. Third, provide an example in using social media and everything related to the internet of think. Abstrak: Tanpa disadari era milenial dengan kecanggihan teknologi membawa peserta didik terpengaruh dengan pergaulan yang salah yang secara tidak sadar akan membawa disintegrasi bangsa. Oleh karena itu guru pendidikan agama kristen dapat memiliki strategi dalam membawa peserta didik membangun kebangsaannya melalaui paradigma integrasi bangsa yang berlandaskan Pancasila. Melalui kemajuan teknologi dan memiliki menggunakan metode kualitatif deskritif dengan pendekatan studi pustaka dapat disimpulkan bahwa strategi guru PAK dalam membangun Pancasila sebagai paradigma integrasi bangsa terhadap peserta didik di era milenial adalah memahami degradasi atau dekadensi moral di era milenial yang terus meningkat. Untuk itu Guru Pendidikan Agama Kristen mengaktualisasikan pandangan Pancasila sebagai dasar pembangunan integrasi bangsa dan juga melihat tidak ada perdebatan teologis dalam nilai Pancasila dalam perspektif  etis teologis. Dari hal tersebut guru memiliki dasar untuk berperan dalam strategi Guru Pak dalam aktualisasi integrasi bangsa di era milenial dengan langkah: Pertama, mampu menumbuhkan  iman peserta didik yang semakin  dewasa. Kedua, mengajarkan untuk saling mengasihi dan membuang segala perundungan, dan prilaku yang tidak benar peserta didik dalam menghormati pemimpin bangsanya. Ketiga, memberikan keteladan dalam mengunakan sosial media dan segala berhubungan dengan internet of things.